Avaliação do efeito de ordenamento atômico nas propriedades da liga de elemento multiprincipal Cr33Co33Ni33 - Bacurau, Vinícius Pereira (2024)
Previously, it was believed that Multi-Principal Element Alloys (MPEAs) were constituted as a random solid solution. However, recent studies have analyzed the contribution of the mixing enthalpy to the Gibbs free energy and its influence on the formation of the phenomenon known as short-range order (SRO). In this context, some research has focused on evaluating the potential of SRO as a new pathway to enhance the mechanical properties in MPEAs. Thus, the objective of this work is to assess the influence of SRO in two compositions, Cr33Co(33-x)Ni(33+x) (x = 0 and 33). The aim is to induce the formation of SRO through isothermal treatments at 475°C for different time intervals, and thereby investigate the microstructural and mechanical property changes caused by this phenomenon. To achieve this, direct evaluations, such as transmission electron microscopy (TEM) and synchrotron X-ray diffraction (SXRD) analyses, were conducted along with indirect measurements, such as mechanical and physical property analysis (specific heat, Cp). Additionally, molecular dynamics (MD) simulations, along with Monte Carlo (MC) simulations and density functional theory (DFT), were used to corroborate the experimental results. Ultimately, the direct analyses did not detect the formation of SRO in either alloy, with only the presence of the ordered Ni2Cr phase observed in the binary alloy. The physical property results detected exothermic and endothermic reactions in both alloys, associated with the order/disorder reaction. The simulations corroborate the presence of SRO in the ternary alloy. Regarding the mechanical property analysis, no changes were observed in the ternary alloy, while in the binary alloy, the Ni2Cr phase led to an increase in hardness and yield strength.